HUKUM PERDATA INTERNASIONAL SEBAGAI SUB SISTEM HUKUM NASIONAL INDONESIA - Romli, Muhammad (Jurnal Al-Wasith : Jurnal Studi Hukum Islam, 2021)
In the globalization era and technology advancement now where technology, social and cultural development has caused unlimited international intercommunication. As a result, national state territorial boundaries barely become a barrier that may create civil problems due to the convergence of legal systems of countries in the world having their unique characteristics. International civil law becomes crucial and unavoidable in order to establish Indonesian national law to respond to legal challenges in the globalization era. This study used legal research method with conceptual approach and international civil law theories as the analysis tool. The legal materials used in this study were normative primary, secondary and tertiary legal materials executed by searching, collecting and literature study to documents conventionally. The result implicitly showed that foreign element in international civil legal cases can be reviewed from two factors. First is personal factor that is a foreign element aimed to the legal subject committing legal action or subject having different nationality. Second, it is territorial factor referring to the place where legal relationship or incident (legal act) is performed abroad and has the same nationality.